2014
DOI: 10.1093/socrel/srt079
|View full text |Cite
|
Sign up to set email alerts
|

Prayer, Attachment to God, and Symptoms of Anxiety-Related Disorders among U.S. Adults

Abstract: Considerable research has examined the relationship between religion and mental health. This study adds to the literature in this area by addressing two main questions: (1) Is the frequency of prayer associated with symptoms of anxiety-related disorders among US adults? (2) Is this association conditional on the nature of individuals' attachment to God? We examine these questions using data from the 2010 Baylor Religion Survey (N ¼ 1,511). Results reveal no meaningful associations between the frequency of pray… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
115
1
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(128 citation statements)
references
References 84 publications
(126 reference statements)
5
115
1
6
Order By: Relevance
“…Anxious attachment, in contrast, was positively correlated with psychiatric symptoms such as general and social anxiety, obsession, and compulsion (Ellison et al 2014). Interestingly, Ellison et al (2014) also found that individuals that pray frequently while perceiving a close relationship with God experienced certain health benefits, while those that pray yet perceive God as distant do not experience the same benefits in return. Bradshaw and Kent (2017) find similar results, suggesting prayer does not have a main effect on psychological well-being in later life, but rather the association is moderated by attachment to God.…”
Section: Religion and Attachment Theorymentioning
confidence: 94%
See 2 more Smart Citations
“…Anxious attachment, in contrast, was positively correlated with psychiatric symptoms such as general and social anxiety, obsession, and compulsion (Ellison et al 2014). Interestingly, Ellison et al (2014) also found that individuals that pray frequently while perceiving a close relationship with God experienced certain health benefits, while those that pray yet perceive God as distant do not experience the same benefits in return. Bradshaw and Kent (2017) find similar results, suggesting prayer does not have a main effect on psychological well-being in later life, but rather the association is moderated by attachment to God.…”
Section: Religion and Attachment Theorymentioning
confidence: 94%
“…Studies have found secure attachment to and intimacy with God to be inversely associated with psychological distress and psychopathology (Bradshaw et al 2008;Bradshaw et al 2010), and positively associated with greater resilience after perceived negative events (Ellison et al 2014). Anxious attachment, in contrast, was positively correlated with psychiatric symptoms such as general and social anxiety, obsession, and compulsion (Ellison et al 2014).…”
Section: Religion and Attachment Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…These mixed results have been evident in cross-sectional investigations and longitudinal studies, with some suspicion and evidence that types (styles) of prayer (e.g., scripted versus unscripted), contexts of prayer (e.g., high-anxiety versus low-anxiety situations), and expectancies about prayer (e.g., beliefs about whether or not prayers can be answered) may account for these variegated findings (Belding et al 2010;Ellison et al 2014;Harris et al 2005;Wiegand 2004). There is some evidence that coordinated communal prayers are especially efficacious in inhibiting depression and anxiety, with such effects being evident in both short-term and long-term time periods (Boelens et al 2009(Boelens et al , 2012.…”
Section: Empirical Backgroundmentioning
confidence: 99%
“…However, Cicirelli (1991a;1991b) has maintained that when adults are separated from their primary caregivers for a long period, a surrogate attachment figure emerges as part of the working model where the adult becomes drawn to an object of attachment that represents the primary caregiver. This symbolic attachment motivates adults to develop religious beliefs in which they perceive a relationship with God or a religious figure as a symbolic attachment -exhibiting attachment religious behaviour in the form of prayer, devotion to a sacred space, reading religious texts, rituals, and so on, to maintain the relationship (Williams & Watts 2014;Ellison et al 2015;Counted & Watts 2017). This symbolic attachment is a representation of a primary caregiver who is unavailable to the individual.…”
Section: Attachment Theory and The Search For A Religious Attachmentmentioning
confidence: 99%